Clinical analysis of cardiac failure in post-myocardial infarction patients - Reddy, R. Jaya Prakash; Reddy, P. Vijaya Narasimha (International Journal of Advances in Medicine, 2018)
Background: Cardiac failure is one of the common complications of Acute Myocardial Infarction. As CAD is the leading cause of death and post MI Cardiac failure also causing increase in rate of Mortality. It directs us to assess the complications of MI and to evaluate the precautionary & preventive steps of cardiac failure. Methods: The present study comprises of 50 cardiac failure patients with history of MI in the past and who presented with myocardial infarction with cardiac failure were included in this study. We excluded the patients who presented with Cardiac failure without Prior history of MI. This hospital based cross sectional study was conducted at Rajiv Gandhi Institute of Medical Sciences (RIMS), Ongole, Prakasam District, Andhra Pradesh. The study was carried out for a period of 1 year with informed consent. Results: In present study majority number of patients (33) show hypokinesia and 10 are found to have dyskinesia and only 4 are akinesia. In this study More than 50% patients are with history of anterior wall involvement. 36(72%) patients have elevated JVP, 34(68%) have cardiomegaly, 38 patients presented with PND. 29(58%) patients are DM and 35(70%) are HTN and only 6(12%) patients are neither DM, nor HTN. Conclusions: Cardiac failure is a common complication after MI. Most common presentations are breathlessness, chest pain, PND, JVP etc. Anterior wall MI on ECG either isolated or associated with other walls is the leading cause of post MI cardiac failure.